2021
DOI: 10.1039/d1ma00101a
|View full text |Cite
|
Sign up to set email alerts
|

Substitutional effects in TiFe for hydrogen storage: a comprehensive review

Abstract: The search for suitable materials for solid-state stationary storage of green hydrogen is pushing the implementation of efficient renewable energy systems. This involves rational design and modification of cheap alloys...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 223 publications
(450 reference statements)
1
54
0
Order By: Relevance
“…As an example of how each of these aspects is investigated in hydrogen storage materials, refer to this ref. 7. Along with the Fig.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…As an example of how each of these aspects is investigated in hydrogen storage materials, refer to this ref. 7. Along with the Fig.…”
Section: View Article Onlinementioning
confidence: 99%
“…6 Intermetallic compounds (such as TiFe and LaNi 5 ) present good hydrogen storage reversibility under near ambient conditions, but they suffer from low gravimetric capacities (due to the presence of heavy elements as in LaNi 5 or unfavorable thermodynamics as for TiFe). 7,8 For a comprehensive review of the recent development on metal hydrides, the reader is also encouraged to check the following ref. 9.…”
Section: Main Definitions and General Overviewmentioning
confidence: 99%
“…Available studies emphasized the characterization of the TiFe alloy, and only a few attempted to optimize the operation pressure range. Ternary phase diagram observations revealed that most of the elemental substitutions (e.g., Mn, Co, Cr, Ni, and Zr) resulted in the formation of secondary phases [3][4][5][6][7][8][9][10] dispersed uniformly in the TiFe-based primary phase [11], which was unavoidable because of the narrow single-phase region of the TiFe phase. The resultant improvement in the initial activation and other hydrogen-storage properties of TiFe alloys was attributed to the presence of these secondary hydrogenabsorbing phases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…and Zr-based. The most known AB compound for hydrogen storage application is the TiFe and its modifications, obtained by substituting Ti or Fe with other metals [41]. TiFe has a high potential for widespread use, since it stores H2 at low pressure and temperature (e.g.30-70 °C and 10-20 bar) and has a good cycle stability at low pressure [42,43].…”
mentioning
confidence: 99%
“…Different strategies have been investigated to overcome this problem, but also to tailor H2 sorption properties. In this regard, Dematteis et al recently reviewed the substitutional effects on hydrogenation properties of TiFe in ref [41]…”
mentioning
confidence: 99%